2019
DOI: 10.1200/jco.2019.37.15_suppl.5034
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 study of pasotuxizumab (BAY 2010112), a PSMA-targeting Bispecific T cell Engager (BiTE) immunotherapy for metastatic castration-resistant prostate cancer (mCRPC).

Abstract: 5034 Background: mCRPC has a poor prognosis and immunotherapies are largely ineffective. PSMA is a promising therapeutic target in mCRPC, and pasotuxizumab is a PSMA x CD3 BiTE that mediates tumor cell killing. Methods: NCT01723475 was a first-in-human, multicenter, dose-escalation study in patients (pts) with mCRPC refractory to standard therapy. Pts received pasotuxizumab as a continuous intravenous infusion in cohorts of 3–4 pts. Dose-escalation followed a continuous reassessment methodology design. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 0 publications
2
40
0
Order By: Relevance
“…BiTEs are a class of novel antibodies that form a link between T cells and tumor cells, permitting T-cell cytotoxic activity and initiating apoptosis of malignant cells. The PSMA/CD3-bispecific BiTE antibody BAY2010112 (AMG212, MT112) has been found to potently suppress tumor growth in preclinical research and was found to have an acceptable safety profile and dose-dependent clinical activity in a Phase I study of 16 patients [ 79 , 80 ].…”
Section: Psma Radioligand Therapy (Rlt)mentioning
confidence: 99%
“…BiTEs are a class of novel antibodies that form a link between T cells and tumor cells, permitting T-cell cytotoxic activity and initiating apoptosis of malignant cells. The PSMA/CD3-bispecific BiTE antibody BAY2010112 (AMG212, MT112) has been found to potently suppress tumor growth in preclinical research and was found to have an acceptable safety profile and dose-dependent clinical activity in a Phase I study of 16 patients [ 79 , 80 ].…”
Section: Psma Radioligand Therapy (Rlt)mentioning
confidence: 99%
“…PSMA is a frequently highly expressed poorly differentiated and castrate-resistant prostate cancer and is infrequently expressed in other tissues, making it an attractive target for prostate cancer treatment [ 71 , 72 ]. The Phase I trial with pasotuxizumab showed dose-dependent PSA responses, with two long-term responses lasting 14 and 19.4 months [ 73 ].…”
Section: Bi-specific T-cell Engagersmentioning
confidence: 99%
“…In a phase I clinical trial, patients with metastatic castration-resistant prostate cancer were treated with Pasotuxizumab. Besides being well tolerated, one of the patients had a marked regression of bone metastases, as measured by PSMA PET/CT [335].…”
Section: Immunotherapy With Bispecific and Trispecific Antibodiesmentioning
confidence: 93%